Alleviating Rural Farmers Poverty through Effective Micro credit: Evaluation of UNDP Intervention in Delta State - Ike , P. C; Uzokwe, U. N (Asian Journal of Agriculture and Rural Development, 2012)
The United Nations Development Programme (UNDP) introduced a micro credit scheme of N9milllion as one of the projects in the Integrated Community Development Programme (ICDP) in Delta state in 2000. UNDP appointed Lift Above Poverty Organization (LAPO) a Micro Finance Institution (MFI) in Nigeria which has developed a successful model of reaching credit to resource poor households that are generally bypassed by government financial institutions as consultants to implement the scheme in the state. This work sought to determine the return to the different economic activities funded with the loan by the beneficiaries, and ascertain the repayment/default rate of the credit programme. Analysis of data collected from 103 beneficiaries of the scheme spread across the three agricultural zones of the state suggests that the productivity of labour was higher than the estimated wage rate and the rate of return was higher than the interest charged on the loan. It is recommended that since the micro credit has been effective in improving the livelihood of the low income house-holds, the government should mobilize adequate donor support on behalf of the micro credit institutions.